PERANAN ORANG TUA DALAM PEMBINAAN DAN PENGEMBANGAN BAHASA PADA ANAK USIA 2-6 TAHUN - Mainizar Mainizar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2013)
One aspect of child development that parents are to be developed is language skills. Because language skills are very important in human life, especially to convey wishes, ideas, and problems encountered in everyday life. Language is the ability to communicate with other, in which the thoughts and feelings expressed in the form of symbols or symbols to express the sense of something. Language is an essential factor that distinguishes man from animals. With human language can position itself as civilized creatures and develop its culture. Language skills in children will develop in accordance with the developmental age. However, the development and progress of language would be better if accompanied by coaching and guidance from parents.Many things can be done in the parent language development in early childhood as pioneered and laid the foundation on child language,motor exercises, habit, maintain and supervise the children and prevent child language disrespectful language, develop language skills through play, and communicate actively in family.